Regulation of Tau Protein on the Antidepressant Effects of Ketamine in the Chronic Unpredictable Mild Stress Model - Wen, Gehua; Yao, Hui; Li, Yanning; Ding, Runtao; Ren, Xinghua; Tan, Yaqing; Ren, Weishu; Yu, Hao; Zhan, Xiaoni; Wang, Xiaolong; Xu, Enyu; Yao, Jun; et al. (Frontiers in Psychiatry, 2019)
Tau is known to play an important role in maintaining microtubule assembly and stabilization, and maintaining the normal morphology of neurons, but several studies have found that chronic stress leads to Tau hyperphosphorylation. A large number of clinical trials have found that ketamine, which is an N-methy-D-aspartate receptor antagonist, produces a rapid, long-lasting, and potent antidepressant effect in patients suffering from major depression. This rapid antidepressant effect of ketamine, which involves many mechanisms, has attracted wide attention. However, the relationship between ketamine’s antidepressant effects and Tau protein has rarely been examined. We used C57BL/6 and Tau KO mice exposed to 42 days of chronic unpredictable mild stress (the CUMS model) to investigate the effect of ketamine on behavioral changes and synaptic functioning of the hippocampus. The results showed that a single treatment with ketamine rapidly relieved the CUMS-induced anhedonic, despair, and anxious behaviors of the C57BL/6 mice. The depressive behaviors were accompanied by increased levels of specific alterations in hyperphosphorylated Tau protein in the cytoplasm and synapses of the hippocampus of the C57BL/6 mice, but ketamine reduced the aggregation of hyperphosphorylated Tau protein only in the synapses. We also found that CUMS exposure reduced the levels of GluA1 and PSD95 in the hippocampus of the C57BL/6 mice and that these deficits were reversed by ketamine. However, the Tau KO mice did not develop any stress-induced depressive behaviors or deficits in hippocampal function. The antidepressant effect of ketamine may decrease the levels of hyperphosphorylated Tau protein in synapses of C57BL/6 mice.